PENGEMBANGAN MODUL-EL BERBASIS LITERASI SAINS PADA MATERI BAKTERI KELAS X SMA - Fitri Qalbina Radhisa; Evi Suryawati; Fitra Suzanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The availability of learning facilities and infrastructure is inadequate in the implementation of independent learning so that the textbooks owned by students cannot be used optimally as learning resources. Therefore, learning resources are needed that can make students play an active role in the learning process. One of the modules is teaching materials that are systematically arranged using language that is easily understood by students. This study aims to develop an electronic module that can be used as an independent learning resource. This research was conducted at the Laboratory of PMIPA FKIP Rian University and SMA N Plus Riau Province in May-September 2021. This Research and Development research used the ADDIE model which consisted of the analysis, design, and development. Data collection instruments in the form of validation sheets and response questionnaires. The validation results obtained an average value of 3.60 in the Very Valid category. The results of the Limited Trial I and the Results of the Limited Trial II obtained an average score of 3.63 and 3.66 in the Very Good category. This study shows that the scientific literacy-based electronic module on the bacterial material developed is valid and feasible to be used as a source of student self-study.Key Words: Bacteria, Science Literacy, Electronic Module